Combinatorial properties of filters and ideals - Cancino Manríquez, Jonathan (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
The research presented in this thesis is about the existence of I-ultrafilters with special combinatorial properties. More concretely, we are interested in the existence of I-ultrafilters, where I is a definable ideal on ω, typically a Borel ideal. In Chapter 1, we address the existence of I-ultrafilters by mean of parametrized diamonds principles. Given a Borel ideal, we define the cardinal invariants z(I) and zfin(I), and then we prove that the corresponding parametrized diamonds, ◊(z(I)) and ◊(zfin(I)), imply the existence of I-ultrafilters and weak I-ultrafilters. Then we proceed to the calculation of the cardinal invariants z(I) and zfin(I) for the most well-known ideals. In Chapter 2, we answer two questions of J. Flašková. The answer to the first question allows us to give a new characterization of the cardinal invariant d, while the second allows us to generalize a theorem of T. Bartoszynski and S. Shelah. In particular, we prove that in the Miller’s model, I-ultrafilters are dense in the Rudin-Blass ordering for any analytic p-ideal I. This result shows at the same time some limitations on possible generalizations of a theorem of C. Laflamme and J. Zhu. The main result of Chapter 3 shows that it is relatively consistent with ZFC that there is no I-ultrafilters for any Fơ ideal I. As a consequence, we obtain answers to several open questions. Particularly, we obtain that it is relatively consistent with ZFC that there is no Hausdorff ultrafilter, which answers a question of M. DiNasso and M. Forti. In Chapter 5, we show some applications of parametrized diamond principles, answering some questions of D. Monk.

La investigación presentada en esta tesis gira alrededor de la existencia de ultrafiltros con propiedades combinatorias especiales. Más concretamente, estamos interesados en cuestiones de existencia de I-ultrafiltros, donde I es un ideal definible sobre ω, típicamente boreliano. En el Capítulo 1, abordamos la existencia de I -ultrafiltros por medio de diamantes parametrizados. Dado un ideal boreliano, definimos los invariantes cardinales z(I) y zfin(I), y probamos que los correspondientes diamantes parametrizados, ◊(z(I)) y ◊(zfin(I)), implican la existencia de I-ultrafiltros y I-ultrafiltros débiles. Después procedemos a calcular los invariantes z(I) y zfin(I) para los ideals más conocidos. En el Capítulo 2, respondemos dos preguntas de J. Flašková. La respuesta a la primer pregunta nos permite obtener una nueva caracterización del invariante cardinal d, mientras que la segunda nos permite generalizar un teorema de T. Bartoszynski y S. Shelah. En particular probamos que en modelo de Miller los I-ultrafiltros son densos en el orden de Rudin-Blass para cualquier p-ideal analítico I. Dicho resultado muestra al mismo tiempo limitaciones en posibles generalizaciones de un teorema de C. Laflamme and J. Zhu. El principal resultado del Capítulo 3 muestra que es relativamente consistente con ZFC que no existen I-ultrafiltros para cualquier ideal I que es Fơ. Como consecuencia damos respuesta a varias preguntas abiertas, y en particular obtenemos que es relativamente consistente con ZFC que no existen ultrafiltros Hausdorff, lo cual responde una pregunta de M. DiNasso y M. Forti. En el Capítulo 5, mostramos algunas aplicaciones de diamantes parametrizados, respondiendo algunas preguntas de D. Monk.
Instituto de Física y Matemáticas. Facultad de Ciencias Físico Matemáticas. Unidad Morelia del Instituto de Matemáticas de la UNAM. Posgrado Conjunto de Doctorado en Ciencias Matemáticas
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6284; info:eu-repo/classification/cti/1; IFM-D-2021-1405; Ultrafiltros Hausdorff; Diamantes parametrizados; Orden de Katetov